Exploring the impact of creative expression through interactive art making on older adults' well-being. Issue 4 (1st October 2016) - Seo, Jinsil Hwaryoung; Geraci, Lisa; Sanchez, Tiffany
ABSTRACT: Research on enhancing healthy aging through art-related activities is a relatively recent phenomenon. We draw inspiration from the ability of interactive art technology to merge electronics into artifacts whose aesthetics are shaped by their craft components. We believe such artifacts hold great potential to engage older adults and significantly improve their daily lives. Therefore, we developed an interactive art-making program for seniors at local assisted-living facilities aimed to enhance cognitive engagement, social connectedness and sense of well-being in older adults. This article examines the physical and mental experience of our participants as they made electronic cards by hand and explores new approaches to electronics construction that leverages the affordances of other related handicrafts.